Development of mathematic model for coffee decaffeination with leaching method - Sukrisno Widyotomo; Hadi K. Purwadaria; Atjeng M. Syarief (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
A simple mathematic model for caffeine kinetic description during the extraction process (leaching) of coffee bean was developed. A nonsteady diffusion equation coupled with a macroscopic mass transfer equation for solvent was developed and them solved analytically. The kinetic of caffeine extraction from coffee bean is depend on initial caffeine content, final caffeine content, caffeine content at certain time, masstransfer coefficient, solvent volume, surface area of coffee beans, process time, radius of coffee bean, leaching rate of caffeine, caffeine diffusivity and a are constan, solvent concentration, activation energy, temperature absolute and gas constant. Caffeine internal mass diffusivity was estimated by fitting the model to an experiment using acetic acid and liquid waste of cocoa beans fermentation. The prediction equation for leaching rate of caffeine in coffee beans has been found. It was found that Dk (m2/sec)=1.345x107—4.1638x107, and kL (m/sec)=2.445x105—5.551x105 by acetic acid as solvent depended on temperature and solvent concentration. The prediction equation for length of time to reduce initial caffeine content to certain concentration in coffee beans has been developed, Caffeine diffusivity (Dk) and masstransfer coefficient (kL) was found respectively 1.591x 107—2.122x107 m2/sec and 4.897x105—6.529x105 m/sec using liquid waste of cocoa bean fermentation as solvent which depend on temperature and solvent concentration. Key words: Coffee, caffeine, decaffeination, leaching, mathematic model.